(untitled) (Research, Society and Development, 2022)
The development and yield of cherry tomato plants subjected to different modes of silicon application were evaluated, as well as the effects of this fertilization on the accumulation of silicon in plants in soilless cultivation. This is a field research of a quantitative nature. The treatments comprised: plants with foliar silicon application, plants that received silicon in the commercial substrate, plants fertilized with foliar silicon and in the commercial substrate, in addition to the control (without silicon application). The experimental design was in randomized blocks. The supply of macro and micronutrients occurred via fertigation. In the diagnosis leaf, total chlorophyll and chlorophyll a and b were read. The fresh and dry mass of shoots, number and weight of fruits, inflorescence and plant height were also analyzed. The content and accumulation of silicon on the surface of leaves collected in the middle third of the plant and fruit epicarp were determined. The data obtained were submitted to analysis of variance by applying the F and Tukey test at 5% probability, when the results were significant. It was concluded that the application of silicon, regardless of the applied mode, did not differ from the control in all parameters evaluated. The application of foliar silicon favored the increase of trichomes on the leaves, suggesting greater protection against herbivory. It is recommended to carry out further research with different sources and concentrations of silicon in order to identify the response of plants and establish the action of this element in the production of cherry tomatoes.